Answer:
thats quadrant 2
Step-by-step explanation:
Answer: Choice B)
2x+5(2x+3) = 3
============================================
Reasoning:
We start with the second equation 2x+5y = 3
Since y = 2x+3 from the first equation, we can replace every copy of y with (2x+3). This replacement is valid because y and 2x+3 are the same.
So that's how we go from 2x+5y = 3 to 2x+5(2x+3) = 3
This replacement is done to get rid of the y variable, and it allows us to solve for x later on.
Answer:
M=1/2 and 1/4
Step-by-step explanation:
I hope this is what you are asking.
Answer:
Hello
Step-by-step explanation:
The domain is limited with 2 lines parallel: -1 ≤ x ≤ 1
and the disk ? (inside of a circle) of center (0,0) and radius 2
